PENGEMBANGAN E-COMIC BERBANTUAN PIXTON PADA MATERI PROGRAM LINEAR DUA VARIABEL - Hermawan, Lendi Ike; Hobri, H; Murtikusuma, Randi Pratama; Setiawani, Susi; Yudianto, Erfan (Kadikma, 2018)
Abstract. Learning media is a tool to deliver the materials to students during teaching and learning process. This study aims to develop e-comic learning media on linear program of two variable. The process of developing this learning media refers to the Thiagarajan model known as the 4-D model which consists of four stages, namely define, design, develop and disseminate. The results of the comic media validation included in the valid criteria with a correlation coefficient value was 0.91. Based on the trials that have been conducted in Class X-MIPA 4 MAN 1 Jember with a total of 24 students, the results of the use of instructional media including the level of practicality are categorized as good with a percentage was 91.2%. Then the effectiveness results of comic media based on cognitive, psychomoto, and affective aspects obtained effectiveness level of "Good" in all aspects. Cognitive aspects show a percentage of students who scored above the standard score was 75%. The percentage on the student observation sheet was 87% in the psychomotor aspect. The last aspect is affective with a percentage was 93.75%. Keywords: E-Comic, Learning media, Linear Program of Two Variable, Thiagarajan model